The Brazilian National System for Water and Sanitation Data (SNIS): Providing information on a municipal level on water and sanitation services - Marilia C. P. Borges; Sérgio B. Abreu; Carlos H. R. Lima; Thaianna Cardoso; Silvia M. Yonamine; Wagner D. V. Araujo; Paulo R. S. Silva; Volnei B. Machado; Valmir Moraes; Tamara J. B. Silva; Vinícius A. Reis; Jo\~ao V. R. Santos; et al. (Journal of Urban Management, 2022)
Basic sanitation services are essential for human development, promoting health and inhibiting the spread of waterborne diseases. The availability of information on water and sanitation services at the local level supports the formulation, implementation and improvement of public policies aimed at advancing the provision of basic sanitation services to the population. In Brazil, the National Water and Sanitation Data System (SNIS), administered by the Ministry of Regional Development (MDR), is the largest information system for water and sanitation services in the country. Here we present the significant aspects of SNIS and offer the most recent results of water and sanitation services in the country, which reveals that water supply is the sanitation service closest to achieve the universalization preconized by the United Nations with almost 93% of the population served. The situation of sanitary sewer services reveals that only 61.9% of the Brazilian population have sewer collection systems, while only 78.5% of the collected volume is actually treated. The remaining 22.5% of the raw sewer is directly disposed in the environment. With respect to the generated sewer, only 49.1% of the volume is treated. The solid waste data show that a large part of the urban population is served by home collection services. The major challenge of this component is to ensure that the final destination is environmentally appropriate, since there are still many dumps that receive waste from different municipalities. The urban drainage data show that most Brazilian municipalities still have deficiencies in the planning of drainage services.
Keywords: 710; Information systems; SNIS; Urban drainage; Waste management; Wastewater; Water and sanitation